2023
DOI: 10.26599/ntm.2023.9130016
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro physicochemical characterization of a novel type of bone-defect-filling granules—BpNcCaP in comparison to deproteinized bovine bone (Bio-Oss ®)

Abstract: As alternatives to autografts, allografts, and xenografts, calcium phosphate (CaP)-based bone-defect-filling materials (e.g., deproteinized bovine bone (DBB, Bio-Oss ® )) are widely used to repair large-volume bone defects (LVBDs) in clinic. However, most of these materials show a very low degradability due to a sintering process in their production. In this study, we synthesized a novel type of granules-biomimetically precipitated nanocrystalline calcium phosphate (BpNcCaP) by developing our previous biomimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…On the other hand, it is imperative to recognize that Sr-BGNs/GNMs foster osteogenic differentiation not only through releasing Sr 2+ but also via liberating other bioactive ions such as silicon, calcium, and phosphorus. Previous studies have elucidated the synergistic interaction between strontium and silicon or calcium ions, which notably augments osteogenic differentiation and angiogenesis. ,, This finding aligns with our RT-PCR outcomes, further demonstrating the cooperative effect of these ions on bone formation. Furthermore, the mechanisms by which Sr-BGNs/GNMs exert their effects in vivo include two principal aspects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, it is imperative to recognize that Sr-BGNs/GNMs foster osteogenic differentiation not only through releasing Sr 2+ but also via liberating other bioactive ions such as silicon, calcium, and phosphorus. Previous studies have elucidated the synergistic interaction between strontium and silicon or calcium ions, which notably augments osteogenic differentiation and angiogenesis. ,, This finding aligns with our RT-PCR outcomes, further demonstrating the cooperative effect of these ions on bone formation. Furthermore, the mechanisms by which Sr-BGNs/GNMs exert their effects in vivo include two principal aspects.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have elucidated the synergistic interaction between strontium and silicon or calcium ions, which notably augments osteogenic differentiation and angiogenesis. 7,30,31 This finding aligns with our RT-PCR outcomes, further demonstrating the cooperative effect of these ions on bone formation. Furthermore, the mechanisms by which Sr-BGNs/GNMs exert their effects in vivo include two principal aspects.…”
Section: Discussionsupporting
confidence: 89%
“…The biocompatibility of a biomaterial is affected by its surface characteristics, such as hydrophilicity and surface roughness 34 . Hydrophilicity is an important property for a bone-defect-filling material, as reported by Xu et al when they synthesized a novel type of bone graft, BpNcCaP granules 35 . They found that BpNcCaP exhibited greater hydrophilicity and a higher propensity to be wetted by bodily fluids following implantation, potentially resulting in enhanced osteoconductivity compared to deproteinized bovine bone (Bio-Oss®).…”
Section: Resultsmentioning
confidence: 92%